Developing a Soccer Player's Performance Index Model for Chinese Professional Football: Integrating Physical Condition, Match Performance and Team Circumstance (Journal of Global Humanities and Social Sciences, 2024)
The study aims to develop a soccer player’s performance index (SPPI) model for Chinese professional football players by integrating their physical condition, match performance, and team circumstances. The model is intended to identify potential talents and address the challenge of evaluating unknown players in player selection. Moreover, the study found a non-linear relationship between age and SPPI, which suggests that future research on Chinese professional soccer players’ aging curves could benefit from using non-linear models. Overall, the findings of this study provide valuable insights for talent identification and player performance evaluation in Chinese professional soccer.